A phase 3, single-arm, open-label study to evaluate the safety, tolerability, and immunogenicity of a 15-valent pneumococcal conjugate vaccine, V114, in a 3+1 regimen in healthy infants in South Korea (PNEU-PED-KOR) - Alvino Maestri; Su Eun Park; Fiona Fernandes; Zhongyi "Lucy" Li; Yae-Jean Kim; Yun-Kyung Kim; Jin Lee; Ji Young Park; Dong Hyun Kim; GyongSeon Yang; Hyunjung Lim; Jin Oh Kim; et al. (Taylor & Francis Group, 2024)
ABSTRACTThere is an ongoing burden of pneumococcal disease in children despite the use of pneumococcal conjugate vaccines (PCVs). This phase 3, open-label, single-arm, multisite, descriptive study was designed to evaluate the safety and immunogenicity of a 3 + 1 regimen of V114 (VAXNEUVANCE™), a 15-valent PCV, in South Korean infants and toddlers. Adverse events (AEs) were reported for 14 d following any vaccination, and throughout the study period for serious AEs. Serotype-specific immunoglobulin G (IgG) response rates (proportion of participants meeting an IgG threshold value of ≥0.35 μg/mL) and geometric mean concentrations (GMCs) for the 15 serotypes at 30 d postdose 3 (PD3) and at 30 d postdose 4 (PD4) were evaluated as endpoints. Healthy infants enrolled at 42-90 d after birth were vaccinated with V114 (N = 57). The most commonly reported AEs were those solicited in the trial. The majority of reported AEs were transient and of mild or moderate intensity. Few serious AEs were reported; none were vaccine related. No participants died nor discontinued the study vaccine because of an AE. V114 was immunogenic for all 15 serotypes contained in the vaccine, as assessed by IgG response rates at 30 d PD3 and IgG GMCs at 30 d PD3 and at 30 d PD4. V114 was well tolerated and immunogenic when administered as a 3 + 1 regimen in healthy South Korean infants and toddlers.